Improvement of particle swarm algorithm based on ultra-dense networking under 5G architecture - Peng Sheng; Zhao Jianbao; Wei Minjie (Dianzi Jishu Yingyong, 2023)
With the development of mobile communication technology, traditional intelligent terminal devices cannot meet the rapidly growing massive data computing requirements. Mobile edge computing provides low-latency and flexible computing solutions for mobile users in the Internet of Things. Considering the limited computing resources on the edge server and the dynamic needs of users in the network, this paper proposes to allocate the transmit power to optimize the transmission energy consumption through the binary particle swarm optimization algorithm. Analyzing request offloading and resource scheduling as a dual decision-making problem, a new multi-objective optimization algorithm based on particle swarm optimization algorithm is proposed to solve the problem. The simulation results show that the binary particle swarm optimization algorithm can save transmission energy and has good convergence. The proposed new algorithm outperforms existing algorithms in terms of response rate and can maintain good performance in dynamic edge computing networks.